Decaffeination process characteristic of Robusta coffee in single column reactor using ethyl acetate solvent - Sukrisno Widyotomo; Sri Mulato; Hadi K. Purwadaria; A.M Syarief (Indonesian Coffee and Cocoa Research Institute, 2009)
Consumers drink coffee not as nutrition source, but as refreshment drink. For coffee consumers who have high tolerance for caffeine, coffee may warm up and refresh their bodies. High caffeine content in coffee beans may cause several complaints to consumers who are susceptible to caffeine. One of the efforts, for coffee market expansion is product diversification to decaffeinated coffee. Decaffeination process is one of process to reduce caffeine content from agricultural products. Indonesian Coffee and Cocoa Research Institute in collaboration with Bogor Agricultural University has developed a single column reactor for coffee beans decaffeination. The aim of this research is to study process characteristic of coffee decaffeination in single column reactor using ethyl acetate (C4H8O2) solvent. Treatments applicated in the research were time and temperature process. Temperature treatment were 50—60OC, 60—70OC, 70—80OC, 80—90OC and 90—100OC. Time treatment were 2 h, 4 h, 6 h, 8 h, 10 h, and 12 h Size of Robusta coffee beans used were less than 5.5 mm (A4), between 5.5 mm and 6.5 mm (A3), between 6.5 mm and 7.5 mm (A2), and more than 7.5 mm (A1). The result showed that decaffeination process with ethyl acetate solvent will be faster when its temperature was higher and smaller bean size. For bean size less than 5,5 mm, decaffeination process by 10% ethyl acetat can be done 8—10 hours in 90—100OC solvent temperature or 12 hours in 60—70OC solvent temperature for 0.3% caffein content. Organoleptic test showed that 90—100OC temperature solvent treatment decreased coffee flavor, which aroma, bitterness and body values were 1.9 each . Key words : Coffee, caffeine, decaffeination, quality, single column.